1989
DOI: 10.1017/s0021932000017843
|View full text |Cite
|
Sign up to set email alerts
|

Nursing behaviour and its relation to duration of post-partum amenorrhoea in an Andean community

Abstract: Nurloa is a high altitude rural Peruvian community characterized by socioeconomic stratification and differential access to the market economy. Nursing practices and the effects of nursing are also stratified; this translates into a risk of menses at 12 months post-partum nearly seven times greater in wealthier than in poorer women.Most nursing occurs in the morning, among those who practise ondemand breast-feeding. Nursing episodes are clustered into sessions; the amount of breast-feeding is regulated by vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 43 publications
5
76
1
1
Order By: Relevance
“…The term bouts, when used in this paper, refers to extended periods of on-demand breastfeeding as reported by mothers during 24 h recall interviews. It is used with the specific purpose of differentiating recalled breastfeeding data from prospective data; since neither the frequency nor duration of suckling episodes during these bouts was known, it was felt that the use of the suckling unit session (as defined by Vitzthum, 1989) to describe such activity was inappropriate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The term bouts, when used in this paper, refers to extended periods of on-demand breastfeeding as reported by mothers during 24 h recall interviews. It is used with the specific purpose of differentiating recalled breastfeeding data from prospective data; since neither the frequency nor duration of suckling episodes during these bouts was known, it was felt that the use of the suckling unit session (as defined by Vitzthum, 1989) to describe such activity was inappropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Jones (1988, 19901, applying the results of research by McNeilly et al (19881, used multiple hazards analysis to demonstrate the effects of both breastfeeding structure and the duration of lactation on the timing of the return to menses postpartum. Vitzthum (1989) and Wood et al (1985) showed that components of individual breastfeeding bouts (the intervals between bouts and the duration of suckling during bouts) may be determined by quite different sets offactors and must therefore be treated independently in analysis. The work of Panter-Brick (1991) and Vitzthum (1988) successfully integrated cultural variables such as labor demands on mothers and economic change into analysis of factors affecting infant feeding practices.…”
Section: The Ecology and Structure Of Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not the only factor influencing fertihty, extended breastfeeding tends to increase birth intervals and decrease fertility through lactational amenorrhea (Dewey et al 1997;Rosetta 1989;Short et al 1991;Taylor et al 1999;Tracer 1996;Vitzthum 1989). However, the common assumption that in preindustrial populations any shift towards agriculture was accompanied by an increased availability of starchy weaning foods and led to the erosion of exclusive, predominant, and prolonged breastfeeding and shortened birth intervals must be questioned in light of these results.…”
Section: Relationships Between Weaning and Demographymentioning
confidence: 99%
“…Poor nutrition, inadequate health care, later age at first marriage, and infant feeding practices are all implicated (cf. De Jong, 1970;Weitz et al, 1978;Dutt, 1980;Goldstein et al, 1983Goldstein et al, , 1984aAbelson, 1984;Hoff, 1984;Kashiwazaki et al, 1988;Vitzthum, 1988Vitzthum, , 1989. Because it is likely that several interacting determinants contribute to lowered fertility in high altitude populations, the controversy regarding cause and mechanism continues.…”
mentioning
confidence: 99%